Jaminan Fidusia dalam Pembiayaan Murabahah: antara Jual Beli dan Hutang Piutang - Nur Hidayah; Moch. Bukhori Muslim; Abdul AA Azis (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2021)
The issue of shifting from sale and purchase transactions to service transactions due to the binding of collateral with a mortgage or fiduciary rights can become a transaction that is null and void. Solving legal issues related to how the concept of binding collateral needs to be seen in an ontological and philosophical scope. The binding of collateral on murabahah financing should be based on the existence of customer obligations for purchases that have not been paid off based on the Sharia Banking Law. The binding of collateral on murabahah transactions can also be carried out with mortgage rights or fiduciary guarantees based on the existence of customer obligations for purchases that have not been paid off as guided by the Mortgage Law and the Fiduciary Guarantee Law which has accommodated the binding of collateral by basing other main agreements other than the main agreement due to accounts payable.